Enviromental stress crack resistance (ESCR) analysis of blow moulded high density polyethylene (HDPE) containers exposed to surface active agents (PANOX 19) - Wan Abdul Rahman, Wan Aizan; Hashim, Shahrir; Toh, Show Chong; Nadarajah, Nadarajah (2002)
ESCR properties of unimodal, bimodal and silane crosslinked bimodal HDPE were investigated as a function of PANOX 19(polyoxyethylated non-ylphenol ether), exposure times in range of 0-1080 hours at 80C in an accordance to the ASTM D2561-95 procedure B. Degradation changes in the three HDPE materials were monitored by ultimate tensile strength, ultimate strain, drop impact test and characterized by DSC,FTIR and SEM. The mechanical properties occured most rapidly starting at 120 hours duration. This unusual phenomenon was corroborated by chemical measurements (crystalinity and melting temperature). Meanwhile SEM was used to examine surfac cracking. From the results, unimodal HDPE shows the best resistance towards the surface-active agent (SAA). Meanwhile bimodal HDPE shows the worst resistance towards the surface-active agent. Both mechanical and chemical analysis indicates that the oxidative degradation process is confined to the exposed surface of the samples. The three HDPE did not fail in the reasonable time under bottle stress crack (BSC) test conditions, but under drop impact test, a brittle failure mechanism was observed on bimodal HDPE and silane crosslinked HDPE. Blow molded HDPE that exhibit a brittle mode at 360 hours is the bimodal HDPE and 480 hours for silane crosslinked bimodal HDPE, which caused the body of the bottles from cracks.